THE USE OF ENGLISH LANGUAGE IN UTILIZING TIKTOK E-COMMERCE FOR OPTIMIZING THE MARKETING OF 'LAMPUNG BANANA CHIPS': A STUDY IN DIGITAL ECONOMY - Yuniarti, Fatma -; Pasya, Dhel Juni (Universitas PGRI Sumatera Barat, 2025)
The rapid development of the digital economy has encouraged the use of social media as an effective marketing tool, with TikTok emerging as a dominant platform. This study aims to analyze the role of English language usage in marketing local food products, specifically Lampung Banana Chips, through TikTok e-commerce. Using a mixed-method approach, the research combines quantitative surveys and qualitative content analysis of TikTok marketing strategies. The findings reveal that integrating English in product descriptions, captions, and voiceovers significantly enhances audience engagement. Accounts that incorporated English in their marketing strategies achieved an average engagement rate of 6.5%, compared to 3.8% for accounts using only Indonesian. Additionally, the use of English in content created a more professional and globally appealing perception of the product, increasing consumer trust and expanding market reach beyond Lampung. This study highlights the importance of language-based marketing strategies in optimizing digital commerce.